2013
DOI: 10.1155/2013/413604
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Leg Ulcers: Epidemiology, Aetiopathogenesis, and Management

Abstract: Chronic leg ulcer is defined as a defect in the skin below the level of knee persisting for more than six weeks and shows no tendency to heal after three or more months. Chronic ulceration of the lower legs is a relatively common condition amongst adults, one that causes pain and social distress. The condition affects 1% of the adult population and 3.6% of people older than 65 years. Leg ulcers are debilitating and greatly reduce patients' quality of life. The common causes are venous disease, arterial disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
257
1
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(281 citation statements)
references
References 38 publications
(74 reference statements)
3
257
1
20
Order By: Relevance
“…Additional treatment with local antibiotics had favourable outcome in wound healing rates similar with previous studies. 1,6,15 All patients in our study received AMAs empirically. 28% of the patients were prescribed with combination AMAs and the remaining patients received monotherapy with a single broad spectrum antibiotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional treatment with local antibiotics had favourable outcome in wound healing rates similar with previous studies. 1,6,15 All patients in our study received AMAs empirically. 28% of the patients were prescribed with combination AMAs and the remaining patients received monotherapy with a single broad spectrum antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…5 The major risk factors being diabetes, smoking and obesity. 6,7 Optimum management of CLUs has a large impact in prevention of foot impairment and amputation rate in patients with leg ulcers. Appropriate management of these patients reduces the financial burden and improves patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The gender distribution was similar to other studies reported from India. [2,10] In the Western world, venous insufficiency constitutes to majority of leg ulcers, but in India, systemic conditions such as diabetes, tuberculosis, atherosclerosis, and leprosy are the main risk factors [3] The comorbid factors apart from being the cause, also adversely affect the prognosis and outcome of treatment. In this study, majority of the ulcers were diabetic.…”
Section: Pseudomonas Aeruginosa 5mentioning
confidence: 99%
“…The prevalence of leg ulceration is approximately 1-2%. [1][2][3] They affect 0.6-3% of those aged over 60 years, increasing to over 5% of those aged over 80 years due to increased risk factors for atherosclerotic occlusion such as smoking, obesity, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In several countries, the primary etiology of these ulcers is the peripheral artery disease of lower limbs, especially venous insufficiency (1) . The latter are called venous or varicose.…”
Section: Introductionmentioning
confidence: 99%